2021
DOI: 10.1186/s10020-021-00344-w
|View full text |Cite
|
Sign up to set email alerts
|

Placental 13C-DHA metabolism and relationship with maternal BMI, glycemia and birthweight

Abstract: Background Fetal docosahexaenoic acid (DHA) supply relies on preferential transplacental transfer, which is regulated by placental DHA lipid metabolism. Maternal hyperglycemia and obesity associate with higher birthweight and fetal DHA insufficiency but the role of placental DHA metabolism is unclear. Methods Explants from 17 term placenta were incubated with 13C-labeled DHA for 48 h, at 5 or 10 mmol/L glucose treatment, and the production of 17 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…While the bulk of endogenous 12 C-AA lipids were PEs (32.8%) and PE-Ps (35.4%), for freshly produced 13 C-AA lipids most were TGs (75.1%), with less found in PEs (2.8%), PE-Ps (6.3%) and PIs (5.9%) ( Figure 1 ). This indicates that TGs made up a much greater proportion of newly synthesized AA lipids, while PE, PE-P and PI phospholipids were produced more slowly consistent with previous findings for other fatty acids (Palmitic acid: PA, Oleic acid: OA and Docosahexaenoic acid: DHA) [ 30 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…While the bulk of endogenous 12 C-AA lipids were PEs (32.8%) and PE-Ps (35.4%), for freshly produced 13 C-AA lipids most were TGs (75.1%), with less found in PEs (2.8%), PE-Ps (6.3%) and PIs (5.9%) ( Figure 1 ). This indicates that TGs made up a much greater proportion of newly synthesized AA lipids, while PE, PE-P and PI phospholipids were produced more slowly consistent with previous findings for other fatty acids (Palmitic acid: PA, Oleic acid: OA and Docosahexaenoic acid: DHA) [ 30 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 88%
“…Our previous work suggested that the maternal metabolic environment in utero programs the response of the placenta to in vitro treatments [ 30 , 38 ]. We therefore tested for associations between maternal BMI, fasting glycemia and 2 h glycemia, with the subsequent alterations in 13 C-AA lipids in response to glucose or myo-inositol or combined treatments in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Villous placental explants were cultured as previously described [ 79 ]. Briefly, five pieces of villous placental tissue were biopsied from five different sites across the placenta.…”
Section: Methodsmentioning
confidence: 99%
“…Maternal obesity is correlated with higher birth weight and is usually associated with n-3 fatty acid deficiency [92]. In utero n-3 PUFA deficiency programs the fetal brain growth and maturation and reduces neuronal and behavioural plasticity in adulthood [93].…”
Section: Maternal Lipid Transport and Metabolism And Fetal Brain Deve...mentioning
confidence: 99%